2018
DOI: 10.1021/acs.cgd.8b00121
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Up Temperature Cycling-Induced Deracemization by Suppressing Nonstereoselective Processes

Abstract: The scale-up of Temperature Cycling Induced Deracemization (TCID) of sodium bromate is feasible provided that two non-stereoselective processes are suppressed. Both nonstereoselective processes occur as a result of insufficient crystal breakage or attrition. In the absence of crystal breakage or attrition during the temperature cycles, large crystals emerge and the resulting small total crystal surface area is unable to sufficiently consume the supersaturation during cooling, resulting in non-stereoselective n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…Hence, a threshold suspension density exists below which nonstereoselective secondary nucleation takes place in addition to stereoselective secondary nucleation. Such a threshold suspension density was also found for sodium bromate and is expected to be system‐dependent.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…Hence, a threshold suspension density exists below which nonstereoselective secondary nucleation takes place in addition to stereoselective secondary nucleation. Such a threshold suspension density was also found for sodium bromate and is expected to be system‐dependent.…”
Section: Resultssupporting
confidence: 53%
“…In turn, the amplitude of the thermal cycles dictates the solid mass that dissolves during each cycle and hence the mass of crystals remaining on partial dissolution. The theoretical fraction of solid mass after heating at a given T h can be quantified according to [Eq. ]: truew=Ct-C*()TnormalhCt-C*()Tnormall …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then there has been many studies on this attrition enhanced ripening for chiral resolution [11,19,20]. In recent years, it has been further demonstrated that a complete deracemization of the solid phase can be achieved via a batch-wise combination of solution racemization and temperature cycling [21][22][23][24]. An industrially easy way to apply temperature cycling-enhanced deracemization was lately proposed where instead of applying temperature cycles, the suspension is circulated between two vessels-one kept at high temperature where partial dissolution of the suspension take place, while the other kept at low temperature to promote crystal growth [25].…”
Section: Introductionmentioning
confidence: 99%